Evaluating Class Programs to Improve Educational Quality at MTsN Kota Madiun (CIPP Evaluative Study) - Majid, Fitri Amalia; Tsani, Iskandar (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2023)
This study aims to describe the results of classroom program evaluation using the CIPP evaluative approach. The research data were obtained through observation, interviews, and documentation. The data analysis technique used data reduction, data display, and conclusion. The results of this study showed that: (1) The Context evaluation included objectives, program legality, and environmental support at MTsN Kota Madiun. (2) The Input evaluation at MTsN Kota Madiun was human resources that were in accordance with the standards and sources of funds that came from the monthly dues of the students that had been agreed upon together. (3) The Process evaluation of the Program at MTsN Kota Madiun included a written test and interview selection process for the prospective students and several routes to be able to join the class program as desired, one of them was through the Try Out route organized by MTsN Kota Madium. (4) The Product evaluation of the class program at MTsN Kota Madiun was besides academic achievement, there was also the achievement of the class program, i.e., the creations created and the development of self-potential based on the expertise of each class program.